CXCL13 Damages Blood Spinal Cord Barrier by Promoting RNF6/Sqstm1‐Ubiquitination Induced Autophagy in Experimental Allergic Encephalomyelitis - Jingjing Han; Rui Hong; Cong Cao; Wanhua Feng; Wei Zhuang; Gui Wang; Jingchao Tang; Ya Yang; Chu Zhang; Aihua Zhou; Xuebin Qu (Advanced Science)
Abstract The damage of blood spinal cord barrier (BSCB) is contributing to the disruption of immune microenvironment within central nervous system during the progression of multiple sclerosis (MS) and experimental allergic encephalomyelitis (EAE). Nevertheless, the underlying mechanisms responsible for barrier impairment remain inadequately understood. Here, by analyzing the protein profiles in peripheral blood serum, chemokine (C‐X‐C motif) ligand 13 (CXCL13) was identified to be increased with the progression of MS and EAE. The absence of CXCL13 resulted in alleviation of EAE symptoms, as evidenced by a reduced clinical score, decreased barrier damage, as well as diminished demyelination and inflammatory response in the spinal cord. In the BSCB model, CXCL13 was found to impair barrier structure and function in a dose‐ and time‐dependent manner, which was associated with exacerbated autophagy in endothelial cells, while the application of autophagy inhibitors partially mitigated this damage. Mechanistically, CXCL13 enhanced the expression of RNF6, an E3 ubiquitin‐protein ligase, facilitating the conjugation to Sqstm1 for the ubiquitination at the K314 residue. These findings suggest that CXCL13 significantly contributes to the impairment of the BSCB by promoting RNF6/Sqstm1‐ubiquitination‐induced autophagy during the progression of EAE, thereby offering a promising diagnostic and therapeutic target for MS.